Brain activity during distention of the descending colon in humans - Hamaguchi, T.; Kano, M.; Rikimaru, H.; Kanazawa, M.; Itoh, M.; Yanai, K.; Fukudo, S. (Neurogastroenterology and motility, 2004)
Brain‐gut interaction is considered to be a major factor in the pathophysiology of irritable bowel syndrome. However, only limited information has been provided on the influence of gastrointestinal tract stimulation on the brain. Our aim in this study was to determine the specific regions of the brain that are responsible for visceral perception and emotion provoked by distention of the descending colon in humans. Fifteen healthy males aged 22 ± 1 participated in this study. Using a colonoscope, a balloon was inserted into the descending colon of each subject. After sham stimulation, the colon was randomly stimulated with bag pressures of 20 and 40 mmHg, and regional cerebral blood flow was measured by [15O] positron emission tomography. The subjects were asked to report visceral perception and emotion using an ordinate scale of 0–10. Colonic distention pressure dependently induced visceral perception and emotion, which significantly correlated with activation of specific regions of the brain including the prefrontal, anterior cingulate, parietal cortices, insula, pons, and the cerebellum. In conclusion, distention of the descending colon induces visceral perception and emotion. These changes significantly correlate with activation of specific regions in the brain including the limbic system and the association cortex, especially the prefrontal cortex.